Neutralizing Antibodies to Adenylate Cyclase Toxin Promote Phagocytosis of Bordetella pertussis by Human Neutrophils - Weingart, Christine L. (American Society for Microbiology, 2000)
A previous study showed that opsonization with human immune serum could either promote or antagonize phagocytosis of Bordetella pertussis by human neutrophils depending on whether the bacteria expressed adenylate cyclase toxin. Opsonization of the wild-type strain inhibited phagocytosis relative to unopsonized controls. In contrast, mutants lacking adenylate cyclase toxin were efficiently phagocytosed when opsonized with human immune serum. In this study, we examined opsonization in the presence or absence of monoclonal antibodies to adenylate cyclase toxin. Addition of neutralizing monoclonal antibodies to adenylate cyclase toxin converted a serum that previously inhibited both attachment and phagocytosis of the wild-type strain to one that increased both attachment and phagocytosis compared to the no-serum control. Monoclonal antibodies that recognize the adenylate cyclase toxin but fail to neutralize activity were without effect. These results suggest that adenylate cyclase toxin inhibits both Fc receptor-mediated attachment and phagocytosis of B. pertussis by neutrophils.